2010
DOI: 10.1111/j.1463-5224.2009.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a rebound tonometer (Tonovet®) in clinically normal cat eyes

Abstract: As the rebound tonometer correlated well with direct manometry in the clinically important pressure range and was well tolerated by cats, it appears suitable for glaucoma diagnosis. The mean IOP obtained with the rebound tonometer was 2-3 mmHg higher than that measured with the applanation tonometer. This difference is within clinically acceptable limits, but indicates that the same type of tonometer should be used in follow-up examinations in a given cat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
99
5
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(126 citation statements)
references
References 28 publications
11
99
5
9
Order By: Relevance
“…There are quite a few studies using applanation tonometry in animals (Priehs et al, 1990;Miller et al, 1990;Miller et al, 1991;Dziezyc et al, 1992;Passaglia et al, 2004;Candia et al, 2010;Gerometta et al, 2010;Ribeiro et al, 2010;Rusanen et al, 2010), but we found no reports on the assessment of the mean IOP in healthy sheep using the applanation tonometer Tonopen XL e . The purpose of this study was to determine the mean IOP in healthy adult sheep using applanation tonometry with Tonopen XL e .…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…There are quite a few studies using applanation tonometry in animals (Priehs et al, 1990;Miller et al, 1990;Miller et al, 1991;Dziezyc et al, 1992;Passaglia et al, 2004;Candia et al, 2010;Gerometta et al, 2010;Ribeiro et al, 2010;Rusanen et al, 2010), but we found no reports on the assessment of the mean IOP in healthy sheep using the applanation tonometer Tonopen XL e . The purpose of this study was to determine the mean IOP in healthy adult sheep using applanation tonometry with Tonopen XL e .…”
Section: Introductionmentioning
confidence: 61%
“…The applanation tonometer has become the most popular instrument used for estimating IOP in many species, and being considered by some researchers as the most accurate and reliable method for estimating IOP in animals (Miller et al 1991;Rusanen et al, 2010). The MacKay-Marg applanation tonometer, which is considered the golden standard in Veterinary Medicine, has no longer been manufactured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although applanation tonometry is considered an accurate and reliable method to measure IOP, it cannot be performed in eyes of animals with small corneal diameter (Rusanen et al 2010, Barsotti et al 2013 or it is not confortable, as it was observed with the Amazon parrot. Previous tonometry studies using the Goldmann tonometer have been reported for birds of prey (11-16. mmHg) and parrots (20-25. mmHg).…”
Section: Discussionmentioning
confidence: 99%
“…In any case, 95-98% of glaucoma cases observed in cats are of secondary character and originate from factors causing changes in aqueous humor flow dynamics, such as uveitis, tumour, trauma and intraocular haemorrhage [4] . The normal IOP value determined using applanation tonometry in cats is 18.4 (±0.67) mm Hg [5] .…”
Section: Introductionmentioning
confidence: 99%